2010
DOI: 10.1159/000315769
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Therapy for Localized Spinal Epidural Follicular Lymphoma

Abstract: Background: Myelopathy due to epidural spinal cord compression is rare in patients with malignant lymphoma and most of these patients are diagnosed with high-grade lymphoma. An epidural growth of low-grade lymphoma is even more unusual. Due to this low incidence, therapeutic experience for this entity is limited. Patients and Methods: We report the outcome of 3 consecutive patients with primary spinal epidural follicular lymphoma (FL). Due to the clinical disorders of the patients and despite the localized dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Most authors prefer to administer chemotherapy in conjunction to radiotherapy (RT) and not alone. [1678] Chemotherapy has been given before RT, after RT, sandwiched between, or administered concomitantly with RT. Various combinations of chemotherapeutic agents have been recommended, cyclophosphamide, vincristine, and prednisone being an integral part of all the combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors prefer to administer chemotherapy in conjunction to radiotherapy (RT) and not alone. [1678] Chemotherapy has been given before RT, after RT, sandwiched between, or administered concomitantly with RT. Various combinations of chemotherapeutic agents have been recommended, cyclophosphamide, vincristine, and prednisone being an integral part of all the combinations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many researchers have sustained that in case of spinal cord or nerve roots compression, a surgical procedure of posterior decompressive laminectomy and stabilization followed by adjuvant local radiotherapy and chemotherapy (CHOP-based chemotherapy) is mandatory. 1,2,27,29,30…”
Section: Discussionmentioning
confidence: 99%
“…For example, many researchers have sustained that in case of spinal cord or nerve roots compression, a surgical procedure of posterior decompressive laminectomy and stabilization followed by adjuvant local radiotherapy and chemotherapy (CHOP-based chemotherapy) is mandatory. 1,2,27,29,30 Other researchers have reported that the sole combination of chemo and radiotherapy, without any surgical procedure, could rapidly reduce compression of the involved neurologic structures. This is even recommended in cases of spinal cord compression by pathologic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[11553] Monnard et al observed local control of 88% and a 5-year overall survival of 69% with combined modality treatment. Among the 20 patients who received RT alone, 11 suffered a systemic relapse, 7 died, and 4 were alive of which 2 still had disease.…”
Section: Combined Modality Treatmentmentioning
confidence: 99%